UMP expands international collaboration network with German Konstanz University of Applied Sciences - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 15 December 2021 - Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with Konstanz University of Applied Sciences (HTWG-Konstanz) Germany in expanding the network of international collaboration and further strengthening the relationship between the two universities.